Foliar application of lanthanum promotes growth and phytoremediation potential Solanum nigrum L. (15th May 2023) - He, Ding; Guo, Ting; Peng, Chunqing; Li, Jining; Wang, Fenghe
Abstract: The hormetic effect of rare earth elements (REEs) has been found in a variety of crops and has been promoting crop growth for decades. Spraying leaves with REEs can enhance the endocytosis of plant roots. The non-selectivity of endocytosis is conducive to the direct absorption of environmental pollutants. The hyperaccumulator Solanum nigrum L . ( S . nigrum ), as a plant with high biomass and heavy metal tolerance, is a good candidate for phytoremediation. La(III), as a typical light REE, also has an obvious hormetic effect on S . nigrum . At 10 μM La(III), the biomass of S . nigrum reached the maximum, which was 89% greater than the control, and La(III) concentration was much lower than the previously reported optimum of 56 μM for general plants. In the present study, enhanced endocytosis after foliar spraying of La(III) was firstly observed in the root cell of hyperaccumulation plants, and La(III) increased the biomass of S . nigrum by improving the photosynthetic system, and promoting nutrient uptake and root development. The antioxidant defense system improved by La(III) contributed to the tolerance of S . nigrum to heavy metals. Applying a reasonable range of La(III) is beneficial to improving S . nigrum growth and tolerance of heavy metals. Compared with spraying deionized water, the translocation factor and bioaccumulation factor value of S . nigrum to cadmium increased by 15% and 21% respectively when spraying 10 μM La(III). Our findings provide a reference for improving hyperaccumulator plant growth and biomass, which improves phytoremediation efficiency. Graphical abstract: Image 1 Highlights: Appropriate foliar dosage of La(III) promoted the growth and biomass of S. nigrum. La(III) enhanced endocytosis in the root cells of S. nigrum. Hydroponic experiments with Cd showed La treatment enhanced phytoremediation potential.